2z-6=-38+6z

Simple and best practice solution for 2z-6=-38+6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2z-6=-38+6z equation:


Simplifying
2z + -6 = -38 + 6z

Reorder the terms:
-6 + 2z = -38 + 6z

Solving
-6 + 2z = -38 + 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-6 + 2z + -6z = -38 + 6z + -6z

Combine like terms: 2z + -6z = -4z
-6 + -4z = -38 + 6z + -6z

Combine like terms: 6z + -6z = 0
-6 + -4z = -38 + 0
-6 + -4z = -38

Add '6' to each side of the equation.
-6 + 6 + -4z = -38 + 6

Combine like terms: -6 + 6 = 0
0 + -4z = -38 + 6
-4z = -38 + 6

Combine like terms: -38 + 6 = -32
-4z = -32

Divide each side by '-4'.
z = 8

Simplifying
z = 8

See similar equations:

| 17x+14y+7k-15=0 | | 18y=12 | | 5+7z=10z+20 | | 2(3+2x)-1=13 | | 10y-2x=-6 | | (8t^2-t-2)(9t^2-8t-1)= | | -2x+3y=-16 | | 5m+4=6cm-8 | | 28-4x=8 | | 7x-20=2x | | 3=2*2+b | | 14-4x=2x | | 8x+5-14x+13y=15x+5y-15z+17k-17y | | 50x^2-50x-1000=0 | | 16x^2+11x-26=0 | | 23t-3=5t+11 | | 4w-3=5w | | 1=-0.1x^2+x+0.1 | | z-3/7=z+1/3 | | y-5/11=2y+5/7 | | (3-m)/7=4 | | (1+d)/5=9 | | 3q+5/2=q+6/5 | | (h-7)/3=8 | | (m-5)/4=6 | | (x+3)/4=5 | | x+3/4=5 | | 3t/4=-18 | | -2t/9=8 | | -2t/=8 | | 3t/10=-9 | | (x+10)(x-13)=0 |

Equations solver categories